Bistable voltage mransition using spin-orbit interaction in a ferromagnet-semiconductor hybrid structure - Koo, Hyun Cheol; Yi, Hyunjung; Chang, Joonyeon; Han, Suk-Hee (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
A traveling electron in the high mobility layer with asymmetric charge distribution induces an effective magnetic field that creates an imbalance of spin-up and spin-down energy levels. If a ferromagnet contacts a two-dimensional electron gas layer, the potential depends on the magnetization direction of the ferromagnetic detector. Two different potential levels can be assigned to "0" and "1" states of nonvolatile memory. This new concept of nonvolatile memory using spin-orbit interaction does not need complex magnetic tunneling layers and additional word writing lines.
Keywords: ELECTRON-GAS; INJECTION; DEVICES